2008
DOI: 10.2174/138161208784480171
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-1 and -2 in the Different Stages of Alzheimers Disease Pathology

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by the deposition of beta amyloid (A ) protein and the formation of neurofibrillary tangles. In addition, there is an increase of inflammatory proteins in the brains of AD patients. Epidemiological studies, indicating that non-steroidal anti-inflammatory drugs (NSAIDs) decrease the risk of developing AD, have encouraged the study on the role of inflammation in AD. The best-characterized action of most NSAIDs is the inhibition of cyclooxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
119
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(125 citation statements)
references
References 103 publications
5
119
0
1
Order By: Relevance
“…As in our results using AD model mice, previous studies with postmortem brain from AD patients showed an increase in COX-1-expressing microglia surrounding Ab plaques (5,6). In addition, COX-2 is expressed in neurons in the early phase of the disease but not in microglia or astrocytes (26).…”
Section: Discussionsupporting
confidence: 86%
“…As in our results using AD model mice, previous studies with postmortem brain from AD patients showed an increase in COX-1-expressing microglia surrounding Ab plaques (5,6). In addition, COX-2 is expressed in neurons in the early phase of the disease but not in microglia or astrocytes (26).…”
Section: Discussionsupporting
confidence: 86%
“…It seems that amyloid-b peptide, which is derived from the longer amyloid precursor protein (APP), is the main stimulator of the inflammatory response found in the brain of AD patients (Sastre et al, 2008), resulting in the presence of activated microglia and astrocytes around neuritic plaques (Rodrigo et al, 2004) and increased levels of inflammatory mediators (Hoozemans et al, 2008). Some current hypotheses suggest that even peripheral chronic infections, such as periodontal episodes, may affect the onset and progression of AD (Kamer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Cyclooxygenase (COX), a membrane-bound protein, is involved in inflammation, angiogenesis, colon cancer and Alzheimer's disease [8,11], and classified into two types, COX-1 and COX-2. Both isoenzymes convert arachidonic acid into multifunctional prostanoids.…”
mentioning
confidence: 99%
“…Both isoenzymes convert arachidonic acid into multifunctional prostanoids. COX-2 enzyme is reported as a key player [11] in neuro-inflammation which is involved in most neurodegenerative disorders by eliciting neuronal death and influencing formation of new neurons [9]. In several tissues, mRNA level of COX-2 was studied and level in the brain was lowest [24], but its expression in brain was not the lowest [35].…”
mentioning
confidence: 99%